Relationship Between Knowledge Level and Diet in Adolescents With the Risk of Diabetes Mellitus in Junior High School: A Cross-Sectional Study - Nurayuda, Nurayuda; Setawati, Setawati; Fortuna, Ajeng Dewi; Rachmadhini, Zhakia; Febrianti, Jeny (STIKes Al-Ma'arif Baturaja, 2025)
Type 2 Diabetes Mellitus (T2DM) is a non-communicable disease with increasing prevalence, including among adolescents. This study aimed to investigate the relationship between adolescents’ knowledge level and dietary habits with the risk of developing T2DM. A cross-sectional descriptive design was used with 30 students from SMPN 1 Tanjung Agung selected through purposive sampling. Data were collected using a structured questionnaire on knowledge and diet, along with blood glucose measurement via glucometer. Chi-Square analysis revealed a significant association between knowledge level and diet with blood glucose levels (p = 0.000). Adolescents with good knowledge and regular dietary habits were 4.25 times more likely to have normal blood glucose levels. These findings highlight the importance of health education and the development of healthy eating behaviors from an early age as preventive strategies against T2DM.